Relevance of PUFA-derived metabolites in seminal plasma to male infertility - Chen, Xiangfeng; Wu, Bin; Shen, XiaoRong; Wang, Xin; Ping, Ping; Miao, Maohua; Liang, Ningning; Yin, Huiyong; Shi, Huijuan; Qian, Jun; Zhang, Tiancheng (Frontiers in Endocrinology, 2023)
Abstract: Background:To identify polyunsaturated fatty acid (PUFA)-derived metabolites in seminal plasma of normozoospermic men that could serve as potential diagnostic biomarkers of infertility. Methods: From September 2011 to April 2012, we obtained seminal plasma from 564 men of childbearing age, residing in the Sandu County, Guizhou Province, China. The donors included 376 men with normozoospermia (fertile: n=267; infertile: n=109) and 188 men with oligoasthenozoospermia (fertile: n=121; infertile: n=67). The samples thus obtained were then analysed by liquid chromatography-mass spectrometry (LC-MS) to detect the levels of PUFA-derived metabolites in April 2013. Data were analyzed from December 1, 2020, to May 15, 2022. Results: Our analysis of propensity score-matched cohorts revealed that the concentrations of 7/26 and 9/26 metabolites differed significantly between fertile and infertile men with oligoasthenozoospermia and normozoospermia, respectively (FDR < 0.05). In men with normozoospermia, higher levels of 7(R)-MaR1 (HR: 0.4 (95% CI [0.24, 0.64]) and 11,12-DHET (0.36 (95% CI [0.21, 0.58]) were significantly associated with a decreased risk of infertility, while higher levels of 17(S)-HDHA (HR: 2.32 (95% CI [1.44, 3.79]), LXA5 (HR: 8.38 (95% CI [4.81, 15.24]), 15d-PGJ2 (HR: 1.71 (95% CI [1.06, 2.76]), and PGJ2 (HR: 2.28 (95% CI [1.42, 3.7]) correlated with an increased risk of infertility. Our ROC model using the differentially expressed metabolites showed the value of the area under the curve to be 0.744. Conclusions: The PUFA-derived metabolites 7(R)-MaR1, 11,12-DHET, 17(S)-HDHA, LXA5, and PGJ2 may be reliably utilized as potential diagnostic biomarkers of infertility in normozoospermic men.